Fragmentation of a PTCDA molecule by electron impact - Shpenik, O.B.; Pylypchynets, O.V.; Zavilopulo, A.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
The dissociative ionization of a 3,4,9,10-perylenetetracarboxilic dianhydride (PTCDA) molecule is investigated by the mass spectrometry method. It has been established that the basic process is the decay of a PTCDA molecule. The most intense in the mass spectrum are the fragment ions perylene core C20H8, its half C10H4, carbon dioxide, carbon monoxide, and atomic oxygen. The appearance energies of fragment ions O+ and CO+ are determined by the least-squares method (E = 10.61 eV for O+); (E = 11.54 eV for CO+). The temperature dependence of the most intense ions formation in the temperature range 320—500 K are measured at an electron energy of 80 eV.